The use of cell salvage in adult cardiac surgery at Queen Alia Heart Institute - Alsmadi, Dya D.; Alhadidi, Abdallah; Alawamleh, Ahmad; Alghawanmeh, Suhaib; Alshobaki, Wael; Mohd, Ashraf F. (International Journal of Advances in Medicine, 2024)
Background: Objective of the study was to determine the incidence of use cell salvage, indications, efficacy in blood conservation and benefits on recovery after adult cardiac surgery. Methods: This is an observational analysis of adult cardiac surgical patients presenting for cardiac surgery at Queen Alia Heart Institute in the period between September 2023 and December 2023. Patients’ demographics, type of surgery (cardiac pathology), comorbidities, preoperative and postoperative laboratory results, blood transfusion requirements, extubation and intensive care unit (ICU) length of stay were recorded and statistically analysed to determine the effectiveness of cell salvage. Patients were divided into two groups: The cell saver group and the no cell saver group for comparison. Results: Data from 141 adult cardiac surgeries is included in this analysis. Indications for cell saver use were recent anticoagulation (41.4%), more complex surgery (20.7%), high risk of bleeding (13.8%), preoperative anaemia (6.9%), intraoperative major bleeding (6.9%), coagulopathy (6.9%) and rare patient blood type (3.45%). Patients from the cell saver group required blood transfusion 2.1% more than the no cell saver group. There was no significant difference in the length of hospitalization between those who had and those who had not cell saver used during surgery (11.9 and 12 days, respectively). Conclusions: Cell saver was used in one fifth of adult cardiac surgeries. Most common indications for cell saver use during cardiac surgery were recent anticoagulation and more complicated cardiac surgery. The use of cell saver had no impact on postoperative haematocrit or overall time of hospitalization.